1988
DOI: 10.1002/bjs.1800751004
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of hepatic hydatid disease

Abstract: The results of surgery in 48 patients with hepatic hydatid disease are described. In 26 out of 32 patients with uncomplicated cysts, conservative surgery with obliteration of the cyst cavity by omentoplasty gave satisfactory results. In contrast, 16 patients with cysts complicated by pyogenic infection or cholangitis required a variety of surgical procedures, including prolonged tube drainage, exploration of the common bile duct, sphincterotomy/plasty and hepatojejunostomy to achieve a satisfactory outcome. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1
9

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 18 publications
2
69
1
9
Order By: Relevance
“…In WHO informal working group on echinococcosis 2010 guidelines, it is stated that possible methods for the treatment of the hydatid cyst have not been compared and there is no "best treatment option" (7). Traditional treatment is surgical; however, mortality (0%-6.3%), complication (12.5%-80%), and recurrence (2.2%-22%) rates of this modality are high (8)(9)(10). Medical treatment alone is not efficient, but it can be used as an adjunct before or after the percutaneous treatment as a prophylaxis for abdominal dissemination (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…In WHO informal working group on echinococcosis 2010 guidelines, it is stated that possible methods for the treatment of the hydatid cyst have not been compared and there is no "best treatment option" (7). Traditional treatment is surgical; however, mortality (0%-6.3%), complication (12.5%-80%), and recurrence (2.2%-22%) rates of this modality are high (8)(9)(10). Medical treatment alone is not efficient, but it can be used as an adjunct before or after the percutaneous treatment as a prophylaxis for abdominal dissemination (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 155 cases of liver hydatid, omentoplasty was associated with a significantly lower incidence of external fistula and infection compared to external drainage [3] . Dawson et al [20] conducted a study involving 48 patients and concluded that omentoplasty is the best technique as it is associated with shorter hospital stay and lower incidence of biliary fistula. In our study, four cysts were drained internally in the form of choledochoduodenostomy in one patient and choledochojejunostomy in three patients.…”
Section: Discussionmentioning
confidence: 99%
“…Partial decompression of the cyst, which is usually at a pressure of 300-700 mm of water [2], prevents explosive spillage [27], Ready availability of multiple wide-tubing suckers is essential, as cyst contents will frequently block suction devices during evacuation [5]. The use of the cryogenic cone or the newer Aaron's suction cone [28] which avoids 278 SHARMA and MOJUMDER MJAFI, 51: 4, OCTOBER 1995 cryogenic damage to the liver capsule and adjacent organs makes deliberate evacuation of the cyst relatively safe but requires a wide thoracoabdominal incision to place the cone on the superio-lateral surface of the liver which is a common location of hydatid cysts.…”
Section: Role Of Scolicidal Agentsmentioning
confidence: 99%
“…There is, however, considerable disagreement about the preferable surgical technique. The major issue of debate is whether complete removal of the peri-cyst is necessary to cure the disease [5,11,12,28,29]. Conservative procedures entail the complete removal of the ectocyst and its contents, if possible by enucleation, to prevent spillage.…”
Section: Controversies In Surgical Strategymentioning
confidence: 99%
See 1 more Smart Citation